Intensi Konsumen Dalam Membeli Produk Ramah Lingkungan Dengan Pendekatan Environmental Awareness - Setiawan, Budi; Messakh, Verren Christine; Maulina, Dwi (PT. Karya Inovatif Nusantara, 2024)
Environmental awareness guides consumers in choosing green products, educates them about nature conservation, and fosters a responsible attitude. This research investigates the relationship between environmental awareness and green product knowledge in encouraging green purchase intention for eco-friendly straw products. The unit of analysis in this research is the individual, with a sample size of 385 respondents selected using purposive sampling techniques. From a green marketing perspective, accumulating green product knowledge through advertising and promotion can influence consumer perception and knowledge, thereby influencing green purchasing behavior. Green product knowledge plays an essential role in forming green purchase intentions, with higher levels of knowledge leading to stronger purchase intentions. However, although environmental awareness can increase consumers' knowledge about green products, it does not significantly influence green purchasing intentions. Environmental awareness does not mediate between green product knowledge and green purchasing intentions.